"They Need to Be Managed:" Hunters' and Ranchers' Narratives of Increased Tolerance of Wolves after a Decade of Wolf Hunting. Issue 6 (3rd June 2022) - Richardson, Jill Eileen
Abstract: How do hunters and livestock producers who report increased tolerance for wolves account for the changes in their attitudes, and how can their perspectives inform researchers' understanding of human conflicts about wolves? I explore this by analyzing interviews with people who live, work, and recreate in the Blackfoot watershed, Montana. All interviewees who reported increased tolerance over time were hunters and ranchers with good relationships with government wildlife officials and close ties to a collaborative nonprofit, Blackfoot Challenge. All who reported increased tolerance attributed their tolerance to the legalization of wolf hunting (sometimes in addition to other factors). Several expressed anger at environmental and animal rights groups who used lawsuits to keep hunting illegal for longer in the state. My data suggests that intolerance for wolves may stem from an injustice frame, a belief that humans bear some blame for causing harm.